Epha2 genotype influences ultraviolet radiation induced cataract in mice. (November 2019) - Dave, Alpana; Craig, Jamie E.; Skrzypiec, Karina; Quinn, Stephen; Barnes, Mary; Di Girolamo, Nick; Mackey, David A.; Burdon, Kathryn P.; de Iongh, Robb U.; Sharma, Shiwani
Abstract: Age-related cataract is the major cause of blindness worldwide. Both genetic and environmental factors contribute to the disease. Genetic variation in the Ephrin type-A receptor 2 ( EPHA2) gene is associated with the risk of age-related cataract in multiple populations, and exposure to ultraviolet-B (UV–B) radiation is a well-established risk factor for the disease. Epha2 knockout and UV-B radiation independently lead to cataract in mice, and UV-B radiation reportedly alters EPHA2 expression in cultured cells. We hypothesised that an interaction between UV-B radiation exposure and Epha2 signalling may influence cataract development. To test this hypothesis, 5-week-old Epha2 +/+ and Epha2 +/− mice (n = 8 per group) were exposed to repeated below-threshold doses of UV-B radiation (0.0125–0.05 J/cm 2 ), before development of Epha2 -mediated cataract. Cataract development was monitored after termination of exposure and at least one month later. Histological analysis of exposed and unexposed lenses was performed to assess pathological changes, and gene expression analysis to investigate the mechanism underlying cataract. Both Epha2 +/+ and Epha2 +/− mice developed UV-B dose-dependent anterior polar cataract; cataract severity in both genotypes of mice exposed to either 0.025 or 0.05 J/cm 2 UV-B was significantly higher than that in matched unexposed mice ( p < 0.05). Histological analysis of lenses of both genotypes of mice exposed to 0.025 or 0.05 J/cm 2 UV-B radiation consistently revealed disruption of the lens architecture. A month after the exposure, cataract severity increased in Epha2 +/+ mice treated with the highest dose of UV-B radiation ( p = 0.03) but remained unchanged in Epha2 +/− mice. Gene expression analysis of lenses of both genotypes of mice showed significant upregulation of the cell proliferation marker Mki67 in Epha2 +/+ ( p = 0.036) but not in Epha2 +/− mice exposed to the highest dose of UV-B radiation compared to matched unexposed mice. In conclusion, this study suggests that repeated exposure to doses of UV-B radiation lower than the single minimum dose required for inducing cataract leads to cataract in wild-type and Epha2 heterozygous knockout mice. Furthermore, this study indicates, for the first time, a potentially favourable effect of partial Epha2 deficiency against UV radiation-induced damage in the lens. Highlights: Chronic exposure to below-threshold doses of UV-B radiation induce cataract in mice. Both wild-type and Epha2 heterozygous mice develop UV-B dose-dependent cataract. Recovery time after UV-B exposure and Epha2 genotype influence cataract severity. Lens epithelial cell proliferation underlies UV-B induced cataract in mice. Partial Epha2 deficiency favours against UV-B induced ongoing damage to the lens.